The Role of Service Institutions for Women and Children in Responding to Domestic Violence Against Women: A Case Study of the Savy Amira Women’s Crisis Center - Muhammad Azmi Syauki; Vania Ardelia (International Conference on Psychology and Education (ICPE), 2025)
This study explores the role of the Savy Amira Women’s Crisis Center (WCC), a non-governmental organization in Surabaya, in supporting women victims of domestic violence. Using qualitative methods, including documentary analysis, interviews, and field observations conducted during a six-month internship, the research reveals how WCC provides trauma-informed and victim-centered services that integrate psychological and legal support. The 2024 report indicates that most reported cases involved psychological, sexual, physical, and economic violence, primarily affecting women aged 25–40 who are economically dependent on perpetrators. WCC’s approach emphasizes confidentiality, emotional safety, and empowerment, tailoring recovery plans to individual needs. The institution also facilitates community outreach and peer support groups to foster resilience and reduce stigma. Findings highlight WCC’s effectiveness in building trust, ensuring confidentiality, and promoting social reintegration through accessible and responsive services. This study affirms the essential contribution of community-based institutions like WCC in advancing protection, empowerment, and systemic change for victims of domestic violence in Indonesia.